School Culture Transformation through Collaborative Leadership Practices - Wina Kurniasih; Sururi Sururi; Suryadi Suryadi (Jurnal Pendidikan (Teori dan Praktik), 2026)
This study examines school culture transformation as a foundation for sustainable teacher professional development by analyzing how collaborative leadership is associated with the development of collaborative cultural practices in Indonesian elementary schools. Using a mixed-methods sequential exploratory design, data were collected from 298 teachers across 51 public schools in Purwakarta District and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that collaborative leadership significantly predicts the development of a collaborative school culture, which in turn is positively related to teacher professional growth and performance. The model explained approximately 30% of the variance in collaborative culture and 38% in teacher performance, with cultural transformation acting as a partial mediator between leadership and teacher outcomes. These results suggest that improvements are associated with processes such as fostering trust and psychological safety, strengthening shared purpose and collective efficacy, and embedding collaborative and reflective routines within school practices. The study concludes that collaborative leadership serves as an important enabling factor in strengthening teacher development and supporting school culture transformation, while emphasizing that such transformation is context-dependent and shaped by broader organizational conditions within Indonesian schools.